Pembentukan Mahkamah Konstitusi Sebagai Pelaku Kekuasaan Kehakiman di Indonesia - Bambang Sutiyoso (The Constitutional Court of the Republic of Indonesia, 2010)
Establishment of the Constitutional Court marks a new era in the power of the judiciary system in Indonesia. Some areas that had not been touched (Untouchables) by law, such as judicial review issues on the Constitution, can now be done by the Constitutional Court, including the authority, other authority provided for in the 1945 Constitution after the amendment. Besides, the existence of the Constitutional Court must also be equipped with a clear organizational structure, adequate procedural law, legal principles and sources of law that the Constitutional Court made reference in carrying out its duties and judicial authority. The emergence of the Constitutional Court as a principal judicial authorities are expected to become entry points which promote the establishment of a modern system of judicial authority in Indonesia.